Comportamento informacional dos estudantes de odontologia: busca e recuperação da informação científica - Oliveira, Cibele Fernandes de [UNIFESP] (2016)
Research on informational behaviour originated from the studies of users and refer to the ways in which individuals deal with information. Afterwards, the informational behaviour was split into information seeking behaviour, seeking behaviour in information systems and information utilization behaviour. On this route to seek information, the individual may interact with manual or computer-based information systems such as database systems. The contribution of these studies are improvements in university libraries information products and services reversed into benefits to the studied group. Each knowledge area includes its specificities and the health area is a rich research environment due to several characteristics, such as: large information flow and the speed that information is updated. This research aimed to identify the information behavior of Dentistry course students, regarding the pursuit of scientific information. This is a descriptive quantitative approach using a sample composed of students enrolled in a Private University Dentistry course in the city of Santos. Data collection has been performed using a structured questionnaire of 23 multiple choice questions. It has been elaborated based on previous studies about information behavior and on the Wilson and Walsh?s information behavior revised model. It has been applied using press format, distributed by the researcher in classroom and filled by the students who agreed to take part on the research by signing of the Terms of Consent. Results show the search for scientific information takes place preferably in electronic media, however, for the reading, they are mainly printed. For choosing a document, students prioritize its relevance, mother tongue and the author?s recognition. Among the most consulted sources of information are the internet search engines, online learning materials and the printed book, which is considered the most reliable and relevant source by students. Databases are rarely used for academic research and students from the year four of graduation are the ones who use them the most. It was also observed that these students are the ones who face more difficulties, firstly to decide which base to use on their research and furthermore which search terms to use. In this context, it is necessary to insert topics of information literacy during the course of graduation. It is suggested it happens since the beginning of the course, intending the development of appropriate skills for the access, evaluation and use of scientific information. Information users should become independent learners, as well as the university library should be consolidated as an University?s educational resource.